Research Progress on the Effect of Addition of Alloy Elements on Electrochemical Migration of Tin - Based Electronic Materials - WANG Hong, WU Ying, LIAO Bo - kai, GUO Xing - peng (Cailiao Baohu)
Tin - based electronic materials are one of the core materials for electronic component packaging and welding. Aiming at the electrochemical migration failure of tin - based electronic materials in service, the main failure forms, electrochemical migration mechanism, research methods, evaluation methods and inhibition methods of tin - based electronic materials were discussed in this paper. Meanwhile, the effects of different alloying elements on the electrochemical migration behavior of tin - based electronic materials were reviewed.